The flat mite Tenuipalpus uvae De Leon (Acari: Tenuipalpidae): descriptions of all stages, ontogeny of setae and morphometric analysis - Nascimento, Renata S.; Castro, Elizeu B.; Tassi, Aline D.; Mineiro, Jeferson L. C.; Carrillo, Daniel; Ochoa, Ronald; Oliveira, Anibal R. (Zootaxa, 2024)
The flat mite Tenuipalpus uvae De Leon, 1962 (Acari: Tenuipalpidae) is restricted to the Americas. The only available descriptions of this mite are based on the holotype and 12 paratype females and nymphs from Mexico. This paper focuses on redescribing the species based on the paratypes and new material from Florida (USA) and Brazil. Additionally, a new specific diagnosis, including characterization of the male, larval stages and eggs, and an ontogenetic/morphometric analysis of all the specimens are provided. Three diagnostic features found in all stages of T. uvae are the seta v2 which is distinctly shorter than the strongly serrated and rodlike sc1–2, while the leg tibiae I–II have three setae each, characteristics unique to T. uvae. Intra and inter-specific morphometric population differences and similarities among females were also described. An important variation observed was a dorsal surface reticulated, with a different morphology of microplates. Interestingly, the female mites that exhibited this feature on the tegument were only observed in the Florida population, suggesting variations observed could be due to aging, environmental conditions or host associations, so further study is needed.